Transmission model for Zika virus between human and mosquitoes - Puntipa Pongsumpun; Puntani Pongsumpun (My University, 2022)
Zika virus is mainly transmitted by mosquitoes. This disease can also be passed through sexually transmission. This disease can be found in South and Central America, the Caribbean, the Pacific islands, Africa, and Asia. Zika virus disease is normally a mild disease. About 80% of infected people do not develop symptoms at all. Transmission of this disease is described by mathematical model. We separated the human into susceptible, infectious and recovered populations. The mosquitoes are divided into susceptible and infectious populations. The transmission model is analyzed by using standard dynamical analysis. Local stability analysis of our transmission model is analyzed. We find the basic reproduction number and the factors which influence the transmission of the disease.
Keywords: Mosquito-borne diseases and control; COVID-19 epidemiological studies; Viral Infections and Vectors